Brain-Derived Neurotrophic Factor Reduces Long-Term Mortality in Patients With Coronary Artery Disease and Chronic Kidney Disease - Hsu, Cheng-Yueh; Sheu, Wayne Huey-Herng; Lee, I-Te (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Chronic kidney disease (CKD) is a risk factor for coronary artery disease (CAD). We examined the effects of circulating brain-derived neurotrophic factor (BDNF) on long-term mortality in patients with CAD and CKD. Methods: We enrolled patients with established CAD in the present study. Serum BDNF and estimated glomerular filtration rate (eGFR) were assessed after overnight fasting. All-cause mortality served as the primary endpoint. Results: All 348 enrolled patients were divided into four groups according to their median BDNF level and CKD status, defined according to eGFR < 60 mL/min/1.73m2. Forty-five patients reached the primary endpoint during the median follow-up time of 6.0 years. Kaplan-Meier survival analysis indicated that the group with low BDNF and CKD had a significantly higher mortality rate than the other three groups (log-rank test p < 0.001). Compared to the high BDNF without CKD group, the low BDNF with CKD group had a hazard ratio (HR) of 3.186 (95% confidence interval [CI]: 1.482‒6.846) for all-cause mortality according to the multivariable Cox proportional hazard regression analysis after adjusting for age and urine albumin-creatinine ratio (p = 0.003). Furthermore, there was a significantly interactive effect between BDNF and CKD status on the risk of the primary endpoint (odds ratio = 6.413, 95% CI: 1.497‒27.47 in the multivariable logistic regression model and HR = 3.640, 95% CI: 1.006‒13.173 in the Cox regression model). Conclusions: We observed a synergistic effect between low serum BDNF levels and CKD on the prediction of all-cause mortality in patients with CAD.